INNOVATIVE PRINCIPLES OF FRESHWATER RESOURCES MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - SERBOV, Nikolay; IRTYSHCHEVA, Inna; PAVLENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
About two-thirds of the world's population may experience water shortages within several decades. Yet, in many countries, there is still a tendency to solve water scarcity problems by increasing water supply, increasing the storage and distribution of surface and groundwater through the creation of new infrastructure, desalination of saline or brackish water, reuse of wastewater, or recharge of aquifers. This trend should prevail over the focus on reducing water demand, for example, by stopping losses in transport and distribution systems, implementing adequate tariff systems aimed at reducing the level of water demand, changing water use technologies, and, in general, increasing the efficiency of water use in household, industrial trial and irrigation systems; in other words, seeking to improve overall water productivity. However, it is possible to overcome the water shortage through efficient and rational use while using innovative solutions that will significantly modernize the water resources infrastructure. Therefore, using creative principles of freshwater resource management in the context of sustainable development should become a perspective for the next ten years. The article aims to research the current state, regional features, and prospects for developing the innovative potential of freshwater resources in Ukraine. It has been proven that in Ukraine, the share of state budget expenditures for environmental protection of total spending ranges from 0.57 to 1.11%. It was determined that the largest share of state budget expenditures on environmental protection in total spending was observed in 2011 - 1.11%, and the smallest in 2020 was 0.57%. It is noted that in 2020, the volume of expenses for environmental protection was significantly reduced compared to the previous year by UAH 675 million. The analysis showed that during the research period, the largest share of expenses was allocated to preventing and eliminating environmental pollution. Therefore, it was determined that the item of budget expenditures for the prevention and elimination of environmental pollution for 2010-2020 increased from UAH 2,255 million to UAH 6,507 million. However, the structure of total expenses decreased slightly from 78.52% to 71.85%, respectively. Accordingly, in the form of costs, the reduction occurred in the following items of budget expenses: preservation of the nature reserve fund from 7.64% in 2010 to 6.78% in 2020, fundamental and applied research and development in the field of environmental protection from 2.06 % to 1.85%, respectively.
Keywords: freshwater resources; innovation; costs; capital investment; sustainable development